2019
DOI: 10.1186/s12872-019-1207-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio in patients with acute myocarditis

Abstract: BackgroundAcute myocarditis (AM) can be defined as an inflammatory disease of the myocardium and characterized by large heterogeneity of clinical presentation. Myocarditis is becoming increasingly recognized as a contributor to unexplained mortality, and is thought to be a major cause of sudden cardiac death in the first two decades of life. The present study aimed to search the assessment of repolarization dispersion measured from the 12-lead surface electrocardiogram (including Tp-e interval, Tp-e/QT and Tp-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Regarding ECG markers of repolarization disturbances, QTc, Tp‐e interval, and TDR have a prognostic significance in the prediction of increased risk of malignant arrhythmia and morality in patients with certain cardiovascular diseases, such as coronary artery disease and myocarditis 22 . ECG changes, such as QTc prolongation, conduction and repolarization abnormalities, and ventricular arrhythmias, may reflect myocardial injury directly or indirectly associated with COVID‐19 pneumonia 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ECG markers of repolarization disturbances, QTc, Tp‐e interval, and TDR have a prognostic significance in the prediction of increased risk of malignant arrhythmia and morality in patients with certain cardiovascular diseases, such as coronary artery disease and myocarditis 22 . ECG changes, such as QTc prolongation, conduction and repolarization abnormalities, and ventricular arrhythmias, may reflect myocardial injury directly or indirectly associated with COVID‐19 pneumonia 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial action potential is represented with the peak of T-wave in ECG and the end of myocardial action potential is represented with the end of the T wave. Therefore, Tp-e interval is an indicator of transmural depolarization 20 , 21 . The prolongation of TP-e interval has been previously demonstrated in Brugada syndrome, long QT syndrome, hypertrophic cardiomyopathy, in conventional smokers, patients with obstructive sleep apnea and Behcet's disease 11 , 15 , 21 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 186 subjects with acute myocarditis the presence of at least one ectopic ventricular beat on the admission ECG, wide QRS complex and long QT segment were associated to cardiac death independently of LVEF at a median follow-up of 55 months [ 67 ]. The relevance of QT interval in identifying subjects at increased risk for ventricular arrhythmias has been recently confirmed in a small report on 56 subjects with acute myocarditis and preserved LVEF [ 68 ]. The investigators also reported an increased T wave peak-to-end interval in subjects with sustained ventricular arrhythmias at follow-up.…”
Section: Risk Stratification Of Scd In Patients With Acute Myocarditismentioning
confidence: 99%